PERAN ORANG TUA DALAM MENUMBUHKAN MOTIVASI BELAJAR ANAK DAN PRESTASI SISWA - Agus Harianto (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
The relationship that exists between parents and children is very close. Children have a close and strong emotional bond with their parents. Unlike the relationship that is formed between a teacher and a child, this relationship will end after the child has finished receiving education. However, the relationship between parents and children will continue even into adulthood. This kind of relationship will continue and is always needed by children. All forms of parental love and attention to children are elements that are needed by children, especially during their growth and development. This paper discusses the role of parents in fostering children's learning motivation and student achievement. From the study conducted, it can be seen that the role of parents in improving children's learning achievement in school is very large. Parents who do not pay attention to their children's education, for example they are indifferent to their child's learning process, do not pay attention to the interests and needs of their children in learning, do not manage their learning time, do not provide or equip learning tools, do not want to know how their child's learning progress is, difficulties experienced by their children in learning and others can cause children to be less or even unsuccessful in learning. The results obtained, grades or learning achievements will not be satisfactory or may even fail. Parents who always pay attention to their children, especially attention to their learning activities at home, make children more active and more enthusiastic in learning because they know that it is not only themselves who want to move forward, but their parents also have the same desire. So that the learning outcomes or learning achievements achieved by students are better.